Synthesis and characterization of the new two-dimensional Heisenberg antiferromagnet double perovskite BaLaCuSbO61. Issue 23 (21st June 2015) - Blanco, M. Cecilia; Paz, Sergio Alexis; Nassif, Vivian M.; Guimpel, Julio J.; Carbonio, Raúl E.
<x xml:space="preserve">Abstract</x> Powder X-ray diffraction patterns, magnetic susceptibility as a function of temperature, and polyhedral representation along the c-axis of the BaLaCuSbO6 double perovskite have been reported.